PENGARUH METODE PROBLEM SOLVING TERHADAP HASIL BELAJAR PADA MATERI EKOSISITEM DI KELAS IV UPTD SD NEGERI 122379 PEMATANGSIANTAR. - Febriani, Devi; Simanjuntak, Hotnauli Cristina; Situmorang, Jennifier Lorensa; Sijabat, Windi Yohana; Purba, Nitciari (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
This study aims to see whether the use of puzzle media has an influence on the mathematical learning outcomes of second grade students in UPTD 122379 Pematangsiantar. This research uses a quantitative approach with the use of a one-group pretest-posttest research design. The location of this research was carried out in UPTD SD State 122379 Pematangsiantar. The sample determination technique used is the total sampling technique. With data analysis techniques: 1. the N-Gain test; 2. two hypothesis tests. The application of puzzle media significantly improved the mathematical learning outcomes of second- grade students. This is demonstrated by an increase in the average student score from 54.16 on the pretest to 83.5 on the posttest. The N-Gain test score of 0.63 showed that the improvement in the learning outcome of students was in the middle category. The test results of the hypothesis, showing a thitung value of 5.74 greater than the ttable (2,045), stated that the zero hypotheses (H0) were rejected and the alternative hypotheses (H1) were accepted. This marks the significant influence of the application of puzzle media on the improvement of mathematical learning outcomes of flat building materials in class I in the State SD UPTD 122379 Pematangsiantar.